Knowledge, Attitude, Epidemiological Risk Factors and Prevention Practices of Japanese Encephalitis in Community Members of Kathmandu and Morang Districts, Nepal (Global Journal of Science Frontier Research, 2019)
A research was conducted among communities' members of Kathmandu and Morang districts to study knowledge, attitude, epidemiological risk factors, and prevention practices of Japanese Encephalitis (JE) based on a questionnaire survey. In this study, 100 pig farmers were surveyed from each district to assess the knowledge, attitude, epidemiological risk factors and prevention practices for Japanese encephalitis virus (JEV) infection. In Kathmandu, 42% pig farmers were aware of JE while in Morang only 25% were having knowing of it; the finding was significantly different (P
Keywords: japanese encephalitis; japanese encephalitis virus; insecticide treated nets; vaccination; communities member; questionnaire; mosquito bite